ANALISIS VEGETASI NEPENTHES SPP. DI HUTAN PENELITIAN UNIVERSITAS BORNEO TARAKAN - Silfia Ilma; Fatchur Rohman; Ibrohim Ibrohim (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract-The research was purpose to find out the species diversity index, evenness index, abundance and dominance Nepenthes spp. in the forests of Borneo Tarakan University. The research explorative-descriptive has been implemented in the forest of Borneo Tarakan University. Sampling using a plot size of 10 x 10 m plots of 150 samples.Vegetation sampling with analysis techniques plot. Data were analyzed using the Shannon-wiener diversity index, evenness index Eveness, and important value index. Results showed the greatest diversity index of 1.05 means that moderate levels of diversity, the spread of the number of individuals of each species being and stability of the community. The lowest diversity is 0.68. Evenness index was highest of 0,76 means that Nepenthes vegetation in a state somewhat balanced. Lowest evenness index is 0,49. Abundance was highest of 367 individuals. Results of the highest importance value index N.ampularia by 105,56%. Keywords: nepenthes, diversity, evenness, dominance